Comparison of Efficacy of Intravenous Amikacin with Intravenous Cefoparazone/Sulbactum in Urinary Tract Infections Caused by Escherichia Coli Indiabetic Patients (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of I/V Amikacin with I/V Cefoperazone/Sulbactum in urinary tract infections caused by Escherichia coli in patients having diabetes mellitus.Study Design: Randomized clinical trial studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Khyber Teaching Hospital, Peshawar during November 2014 to April 2015.Materials and Methods: It was a randomized clinical trial and the sample size was 46 patients in each group, total sample size was at least n=92.Non probability consecutive sampling was used for sample collection. Routine investigations like Full Blood Count, Ultrasound of Urinary system, Renal Function tests, 24 hours urinary proteins and creatinine clearance, Random and fasting blood Sugar and HbA1c were done on the selected patients.The patients were then divided into two groups “Group-A’ for Amikacin I/V 500mg BD and ‘Group-B’ for Cefoperazone/Sulbactam 2 Grams I/V BD, both groups receiving treatment for 07 days. The diagnosis of UTIs was based on mentioned criteria. Urine culture was performed by collecting clean-catch midstream urine in a sterile urine bottle or sending catheter tip, if patient was catheterized and then subjecting it to growth for bacteria using kled or MacConkey agar incubated at 37C˚ in incubator for 24 hours in hospital laboratory. At the end of study, difference of atleast 10% in Efficacy of two groups(drugs) was considered as significant. P1=Efficacy of Amikacin (90%) andP2=Efficacy of Cefoperazone/Sulbactam(65%), Power of test(1-β)=90% and level of significance=0.05%.Results: Our study shows that mean age in group A (I/V Amikacin) was 44 ± 2.77 years and mean age in group B (I/V Cefoperazone/Sulbactum) was 46± 3.12 years. In group A (I/V Amikacin) 32% patients were male, 68% patients were female. Whereas in group B (I/V Cefoperazone/Sulbactum) 30% patients were male, 70% patients were female. More over our study shows that I/V Amikacin was effective in 85% patients and was not effective in 15% patients whereas I/V Cefoperazone/Sulbactum was effective in 68% patients and was not effective in 32% patientsConclusion: Our study concludes that I/V Amikacin was more effective than I/V Cefoperazone/sulbactam in urinary tract infections caused by Escherichia Coli in diabetic patients.